Pediatric psychopharmacology : principles and practice - Martin, Andrés (Oxford University Press, 2003)
This is a comprehensive text on the use of medication in the treatment of children and adolescents with serious neuropsychiatric disorders. It reconciles recent research findings with good clinical practice.